ChemInform Abstract: Recent Advances in Osmium‐Catalyzed Hydrogenation and Dehydrogenation Reactions. Issue 18 (May 2015) - Chelucci, Giorgio; Baldino, Salvatore; Baratta, Walter
Abstract Review: 39 refs.